Long-term clinical outcomes after treatment of stent restenosis with two drug-coated balloons. Issue 8 (December 2018) - Schröder, Jörg; Vogt, Felix; Burgmaier, Mathias; Reith, Sebastian; Almalla, Mohammad
Abstract : Background: Treatment of in-stent restenosis (ISR) is still a clinical challenge in interventional cardiology. Paclitaxel-coated balloons (PCBs) are an attractive therapeutic option for ISR. There are several different types of PCBs available for percutaneous coronary intervention, but to date, comparative data between different types of PCBs for the treatment of ISR are scarce. Patients and methods: This single centre, nonrandomized, retrospective study under real-world condition included 194 patients with 194 ISR treated by repeat percutaneous coronary intervention with PCBs. The primary end point was major adverse cardiac events (MACEs), defined as cardiac death, myocardial infarction and need for target lesion revascularization (TLR) at 1 year. Secondary end points were MACE and TLR at long-term follow-up. Results: Baseline clinical and angiographic parameters were comparable between the two groups. Patients in the iopromide-based PCB and butyryl-tri-hexyl citrate (BTHC)-PCB groups were followed up for 32.2±20.5 and 24.2±13.3 months, respectively ( P =0.001). MACEs at 1-year follow-up were 15.0 and 15.8% ( P =0.879) for the BTHC-PCB and iopromide-based PCB groups, respectively. TLR, myocardial infarction and cardiac death for BTHC-PCB versus iopromide-based PCB at 1-year follow-up were 9.6 versus 11.8%, P =0.622; 5.3 versus 3.9%, P =0.640; and 5.3 versus 3.9%, P =0.640, respectively. If complete follow-up periods were included in the analysis, BTHC-PCB and iopromide-based PCB had comparable rates of MACE ( P =0.835) and TLR ( P =0.792). Conclusion: BTHC-PCB and iopromide-based PCB had comparable rates of MACE and TLR for the treatment of ISR at 1-year and long-term follow-up.